Novel Echinacea formulations for the treatment of acute respiratory tract infections in adults—A randomized blinded controlled trial - Sumer, Johannes; Keckeis, Karin; Scanferla, Giulia; Frischknecht, Manuel; Notter, Julia; Steffen, Ana; Kohler, Philipp; Schmid, Patrick; Roth, Bianca; Wissel, Kerstin; Vernazza, Pietro; Klein, Peter; et al. (Frontiers in Medicine, 2023)
Background: Echinacea purpurea has clinical antiviral activity against respiratory viruses and modulates immune functions. Here we compared higher doses of new Echinacea formulations with conventional formulations at lower, preventive doses for therapy of respiratory tract infections (RTIs). Methods: In this randomized, blinded, controlled trial healthy adults (n=409) were randomized between November 2018 and January 2019 to one of four Echinacea formulations, which were taken in case of an RTI for up to 10 days.New formulations A (lozenges) and B (spray) delivered an increased dose of 16800mg/d Echinacea extract during days1-3 and 2240-3360mg/d afterwards; as controls conventional formulations C (tablets) and D (drops) delivered a lower daily dose of 2400mg, usually taken for prevention.Primary endpoint was time to clinical remission of first RTI episodes based on Kaplan-Meier analysis of patient-reported, investigator-confirmed, respiratory symptoms assessed for up to 10 days. In a sensitivity analysis, mean time to remission beyond day 10 was calculated extrapolating treatment effects observed on days 7-10. Results: 246 participants (median age 32 years,78% female) treated at least one RTI. Recovery by day 10 (complete absence of symptoms) was achieved in 56% and 44% of patients with the new and conventional formulations, respectively, showing median time to recovery of 10 and 11 days, respectively (p=0.10 in intention-to-treat analysis, p=0.07 in per-protocol analysis). In the extrapolated sensitivity analysis, new formulations resulted in significantly shorter mean time to remission (9.6 vs. 11.0 days, p<0.001). Among those with an identified respiratory virus, viral clearance until day 10 based on real-time PCR from nasopharyngeal swabs was more frequent with new formulations (70% vs. 53%, p=0.046). Tolerability and safety (adverse events: 12% vs. 6%,p=0.19) were good and similar between formulations. There was one severe adverse event with a potential hypersensitivity reaction in a recipient of the novel spray formulation. Conclusions: In adults with acute RTI, new Echinacea formulations with higher doses resulted in faster viral clearance than conventional formulations in prophylactic dosages. The trend for faster clinical recovery was not significant by day 10 but became so upon extrapolation. Dose increase during acute respiratory symptoms might improve clinical benefits of orally administered Echinacea formulations.